FACS-array–based cell purification yields a specific transcriptome of striatal medium spiny neurons in a murine Huntington disease model - Miyazaki, Haruko (J Biol Chem, 2020)
Huntington disease (HD) is a neurodegenerative disorder caused by expanded CAG repeats in the Huntingtin gene. Results from previous studies have suggested that transcriptional dysregulation is one of the key mechanisms underlying striatal medium spiny neuron (MSN) degeneration in HD. However, some of the critical genes involved in HD etiology or pathology could be masked in a common expression profiling assay because of contamination with non-MSN cells. To gain insight into the MSN-specific gene expression changes in presymptomatic R6/2 mice, a common HD mouse model, here we used a transgenic fluorescent protein marker of MSNs for purification via FACS before profiling gene expression with gene microarrays and compared the results of this “FACS-array” with those obtained with homogenized striatal samples (STR-array). We identified hundreds of differentially expressed genes (DEGs) and enhanced detection of MSN-specific DEGs by comparing the results of the FACS-array with those of the STR-array. The gene sets obtained included genes ubiquitously expressed in both MSNs and non-MSN cells of the brain and associated with transcriptional regulation and DNA damage responses. We proposed that the comparative gene expression approach using the FACS-array may be useful for uncovering the gene cascades affected in MSNs during HD pathogenesis.